Unraveling the Determinants of Microcredit Interest Rate - Mohd Ruslan, Rafiatul Adlin; Shafiai, Syahiru; Chua, Mei-Shan; Mohd Roslen, Siti Nurhidayah (Information Management and Business Review, 2023)
The introduction of microcredit has drawn significant attention to the interest rates charged by microfinance institutions, capturing the interest of policymakers worldwide. Despite the competitive nature of the microfinance market, borrowers still bear the burden of relatively high interest rates. Similar to other loans, microcredit requires repayment, and the interest rate is determined by various factors. Nevertheless, acknowledging that the interest rate is intrinsically linked to the risk associated with microcredit is essential. Microfinance institutions often deal with borrowers from low-income backgrounds, making the repayment process inherently riskier. This study aimed to address the crucial question concerning the factors influencing microcredit loan rates, an area that has not been extensively studied. Since the respondents are SMEs, they have been questioned about the interest rates charged to them. If the enterprises have a well-established track record, opt for short-term loans with smaller amounts, and maintain accurate accounting records, the lender may consider offering a lower interest rate. Understanding the determinants of interest rates helps in segmenting borrowers based on their risk profiles. Policymakers and regulators can use the insights from the study to develop appropriate regulations that balance the need for financial inclusion with consumer protection. Additionally, educating borrowers about the determinants of interest rates, how they are calculated, and ways to improve their creditworthiness can empower them to make informed financial decisions and negotiate better terms.